2019
DOI: 10.3390/en12030568
|View full text |Cite
|
Sign up to set email alerts
|

HIRA Model for Short-Term Electricity Price Forecasting

Abstract: In competitive power markets, electric utilities, power producers, and traders are exposed to increased risks caused by electricity price volatility. The growing reliance on renewable sources and their dependence on weather, nuclear uncertainty, market coupling, and global financial instability are contributing to the importance of accurate electricity price forecasting. Since power markets are not all equally developed, different price forecasting methods have been introduced for individual markets. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
(32 reference statements)
0
22
1
Order By: Relevance
“…Medium-term price forecasts (MTPF) range from a week to a few months and is generally required for generation expansion planning, maintenance scheduling, bilateral contacting, fuel contacting, developing investment and hedging strategies [8]. On the other hand, long-term price forecast (LTPF) generally covers time from several months to a few years and is generally used for planning and investment profitability analysis, such as making decisions for future investments in power plants, inducing sites and fuel sources [9]. As in many electricity markets daily prices are determined the day before the physical delivery by means of hourly concurrent auction, STPF has received higher attention in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Medium-term price forecasts (MTPF) range from a week to a few months and is generally required for generation expansion planning, maintenance scheduling, bilateral contacting, fuel contacting, developing investment and hedging strategies [8]. On the other hand, long-term price forecast (LTPF) generally covers time from several months to a few years and is generally used for planning and investment profitability analysis, such as making decisions for future investments in power plants, inducing sites and fuel sources [9]. As in many electricity markets daily prices are determined the day before the physical delivery by means of hourly concurrent auction, STPF has received higher attention in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of the method is that neural network architecture is designed through heuristic methods. [14] used a Hybrid neural model (HIRA model) for Short-Term Electricity price forecasting, which was also applied and tested in the scope of two eletricity markets: German and Hungarian. In Hungary, thermal plants have 90% of installed capacity and represent a stable source of electricity, but generally involving a large installed capacity per unit.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, we compared the average percentage error obtained by our system with the HIRA method [14], which was also applied and tested on two eletricity markets: German and Hungarian. It can be concluded from the results presented in section 2.3.2 that the LSTM Network can predict the value of the PLD with an error of up to 1.44%, which is lower than the value generated from multilayer perceptron networks and HIRA model [14].…”
Section: South Region North Region Rmse Mae Mape Rmse Mae Mapementioning
confidence: 99%
“…Reforms of liberalizing power industry started in Norway, United Kingdom, United States, and Chile in the late 1980s [3]. Technology advancement in the generation and in power networks, have enabled a separation of what had previously been a natural monopoly [4]. Borenstein and Bushnell in 2015 [5] as well as Newbery in 2004 [6] concluded that restructuring of electricity sector did not fulfill all expectations as costs overweighed the benefits.…”
Section: Introductionmentioning
confidence: 99%